Synthesis of Cubic Phase-Co Microspheres by Mechanical Solid-State Reaction-Thermal Decomposition and Research on Its Growth Kinetics - Ying Deng; Yanhua Zhang; Lingling Peng; Xiaolong Jing; Hui Chen (Advances in Materials Science and Engineering)
Cubic phase cobalt (Co), which can be used as a key component for composite materials given its excellent ductility and internal structure, is not easy to obtain at room temperature. In this study, oxalic acid and cobalt nitrate are used as raw materials to synthesize the cobalt oxalate precursor, which has a stable structure with a five-membered chelate ring. Cobalt oxalate microspheres, having a high internal energy content, were prepared by using mechanical solid-state reaction in the presence of a surfactant, which can produce spherical micelles. The thermal decomposition of the precursor was carried out by maintaining it in a nitrogen atmosphere at 450°C for 3 h. At the end of the procedure, 100 nm cubic phase-Co microspheres, stable at room temperature, were obtained. Isothermal and nonisothermal kinetic mechanisms of cobalt grain growth were investigated. The cubic-Co grain growth activation energy, Q, was calculated in this study to be 71.47 kJ/mol. The required reaction temperature was low, making the production process simple and suitable for industrial applications.